Critical conditions for jumping droplets - Vo, Quoc (2019)
A droplet initially overstretched on a solid substrate pulls back to lower the contact area and may jump away from the substrate. The condition to realize such macroscopic behaviors is often dictated by microscopic characteristics, such as contact-line pinning, in nontrivial ways. Here we theoretically and experimentally reveal the hidden contribution of contact-line pinning in forming the critical condition for detachment of a droplet from a solid substrate, among other dominating hydrodynamical effects. Our results demonstrate the relation between classical theories on contact-line pinning and various droplet manipulating applications in microfluidics and bioprinting.